2016
DOI: 10.1111/ijpo.12174
|View full text |Cite
|
Sign up to set email alerts
|

Influence of maternal physical activity on infant's body composition

Abstract: Exercise intensity modulates neonatal body composition. The long-term significance of a reduced BW, adiposity and BMC with VPA requires further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 36 publications
(50 reference statements)
1
20
0
Order By: Relevance
“…Crucially, we found that cord-blood leptin concentration (a valid biomarker of birth total fat mass [50]) was markedly lower in Pakistani-origin women who were somewhat active as opposed to inactive. Studies using lab-based techniques such as DXA and densitometry have likewise reported lower fat mass and body fat percentage in babies born to women who were more active during pregnancy [51,52]. In line with other largescale population-based studies [53,54] and smaller studies incorporating accelerometry [55], we found no indication that physical activity adversely affected gestational age or birth weight.…”
Section: Neonatal Delivery Outcomes and Body Compositionsupporting
confidence: 87%
“…Crucially, we found that cord-blood leptin concentration (a valid biomarker of birth total fat mass [50]) was markedly lower in Pakistani-origin women who were somewhat active as opposed to inactive. Studies using lab-based techniques such as DXA and densitometry have likewise reported lower fat mass and body fat percentage in babies born to women who were more active during pregnancy [51,52]. In line with other largescale population-based studies [53,54] and smaller studies incorporating accelerometry [55], we found no indication that physical activity adversely affected gestational age or birth weight.…”
Section: Neonatal Delivery Outcomes and Body Compositionsupporting
confidence: 87%
“…Such an increase is supported by the higher cardiac mass in the offspring from endurance-trained mothers as heart mass has been reported to be correlated with lean body mass (Daniels et al, 1995). This is supported by the literature showing that moderate maternal physical activity during gestation is associated with an increase in placental size and function and higher blood volume (Clapp, 2006), which may explain the increase in lean mass (Bisson et al, 2017). Moreover, endurance training during pregnancy is known to improve insulin sensitivity and to reduce circulating insulin levels in mothers (Embaby et al, 2016).…”
Section: Discussionmentioning
confidence: 62%
“…Other evidence also suggests that the first trimester might be a sensitive period for fetal growth programming, with excessive weight gain during the first half of pregnancy associated with increased neonatal weight and adiposity 32. We also recently reported that vigorous physical activity assessed by accelerometry in the first half of pregnancy was an independent predictor of neonatal adiposity, regardless of subsequent physical activity practice 33. Thus, beyond an effect on birth weight, maternal physical activity in early pregnancy may also influence infant’s body composition, which may have a long-term beneficial impact on childhood obesity risk 34…”
Section: Discussionmentioning
confidence: 74%